2022
DOI: 10.3390/ijerph192114516
|View full text |Cite
|
Sign up to set email alerts
|

Current Research Trends, Hotspots, and Frontiers of Physical Activity during Pregnancy: A Bibliometric Analysis

Abstract: Purpose: Physical activity (PA) during pregnancy has been proven beneficial to pregnant women, with a significant effect on ameliorating many severe gestational complications. This work aimed to reveal current research trends, hotspots, and future frontiers in PA during pregnancy. Methods: Software CiteSpace was used to perform a bibliometric analysis with 1415 publications in the Web of Science Core Collection. Results: the number of published papers on PA during pregnancy has increased gradually by year. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…This is a large increase from the prior review, which summarized postpartum PA guidelines from 5 countries published up to 2009. 30 In the past decade, much new scientific evidence has been published on the benefits and risks of postpartum PA and SB, 60 so the increase is not surprising. In the current review, all postpartum guidance provided recommendations on PA, and half provided brief recommendations or statements on SB.…”
Section: Discussionmentioning
confidence: 99%
“…This is a large increase from the prior review, which summarized postpartum PA guidelines from 5 countries published up to 2009. 30 In the past decade, much new scientific evidence has been published on the benefits and risks of postpartum PA and SB, 60 so the increase is not surprising. In the current review, all postpartum guidance provided recommendations on PA, and half provided brief recommendations or statements on SB.…”
Section: Discussionmentioning
confidence: 99%
“…We envision our bibliometric analysis as the Google Maps of research (34) as it works as a network server that offers an aerial view of research, (35) allows policy makers to take decisions according to identified abandoned and neglected areas (as an analogy to knowledge gaps), (36) shows where everybody is crowded (as an analogy of what are the main interests in the scientific field) (37) and predicts where you should go in the future (38) (focus on the most prevalent pathologies in medical consultation).…”
Section: Discussionmentioning
confidence: 99%
“…We see our bibliometric analysis as a type of Google Map for research [ 25 ]. Like a web mapping platform, it provides an aerial view of research [ 26 ], which can help policymakers identify neglected areas (analogous to knowledge gaps) [ 27 ], pinpoint where researchers are most active (analogous to areas of scientific interest) [ 28 ], and predict where future research should focus [ 29 ], such as on the most prevalent pathologies in medical consultations.…”
Section: Discussionmentioning
confidence: 99%